Determination of Vanadium in Water and Biological Samples Using N-Hydroxy-N-o-Tolyl-N'-(2-Methyl)-Phenyl-Benzamidine Hydrochloride and 4-Hydroxy Benzaldehyde - Mishra, Alok; Khan, Shahbaz; Hemlata Mohabey, Ms. (Asian Journal of Chemistry, 2010)
A simple rapid and sensitive method has been developed for the detection and spectrophotometric determination of vanadium(V) in water samples and biological samples. N-Hydroxy-N-o-tolyl-N'-2 methyl phenyl benzamidine hydrochloride reacts with vanadium(V) in presence of 4- hydroxy-benzaldehyde giving deep green-blue complex which is quantitatively extractable at pH 2.3 to 5.1. The Sandell's sensitivity of the reaction is 0.0061 μg/cm-2 at 580-590 nm, with molar absorptivity 8280 ± 50 L mole-1 cm-1 . Mo(V), Fe(III), Co(II) and Ni(II) etc. do not interfere with the determination. The limit of identification of the spot test based on this colour reaction is 0.1 μg of vanadium with dilution limit 1 : 1 x 106.